Conceptual definition and framework of climate change and dust storm adaptation: a qualitative study - Salehi, Shiva (J Environ Health Sci Eng, 2019)
Climate Change Adaptation (CCA) is a complex, multi-disciplinary, and culture-dependent concept. This study aims to explore a conceptual definition, the subjective framework of CCA including its domains, attributes, and consequences. The approach of qualitative conventional content analysis was considered for the explanation of the subjective concept, and at the same time as the collection process, data analysis was performed using Zhang and Wildemuth’s method. The interview method was semi-structured and sampling was targeted and with maximum diversity. The interview was conducted with 22 qualified experts. The accuracy and validity of the data were ensured using Guba and Lincoln scientific accuracy criteria. Six main categories including “sustainability, productivity, stability, empowerment, transformation, and flexibility” were conceptualized in the theme of adaptation characteristics. “Sustainable development, life improvement, response coordination and integration, creativity and innovation, resilience promotion, vulnerability reduction, effective management, and independence” were the main categories in the theme of the adaptation consequences. According to the results, the following conceptual-functional definition can be presented for adaptation to climate change: “CCA refers to the ability of system instability, sustainability, empowerment, productivity, flexibility, and transformation to climate change through the optimal use of resources, resistance, and coping, capacity building and opportunity creation”. This definition is conceptual, it means that includes the main features of climate-adaptation and is also functional that is, includes adaptation strategies for climate change.